CD24 suppresses malignant phenotype by downregulation of SHH transcription through STAT1 inhibition in breast cancer cells. Issue 1 (28th April 2016) - Suyama, Kumi; Onishi, Hideya; Imaizumi, Akira; Shinkai, Kentaro; Umebayashi, Masayo; Kubo, Makoto; Mizuuchi, Yusuke; Oda, Yoshinao; Tanaka, Masao; Nakamura, Masafumi; Katano, Mitsuo
Highlights: CD24 suppresses proliferation and invasiveness in breast cancer cells. CD24 inhibits Hedgehog signaling activation through downregulation of SHH expression. CD24 suppresses SHH transcription through inhibition of STAT1. CD24 gene transfer or STAT1 inhibition may be new cancer treatments in breast cancer. Abstract: Hedgehog (Hh) signaling has been found to be activated in breast cancer stem cells (BCSCs). However, the precise role of the BCSCs marker, CD24, remains unclear. Here, we describe a relationship between CD24 and Sonic Hedgehog (SHH), and reveal a role for this relationship in the induction of a malignant phenotype of breast cancer. CD24 siRNA-transfected breast cancer cells (BCCs) demonstrated higher expression of SHH and GLI1, increased anchorage-independent proliferation, and enhanced invasiveness and superior tumorigenicity compared with control. Conversely, CD24 forced-expressing BCCs possessed decreased SHH and GLI1 expression, anchorage-independent proliferation, and invasiveness. Suppression of SHH decreased invasiveness through inhibition of matrix metalloproteinase (MMP)-2 expression, GLI1 expression, anchorage-independent proliferation, tumorigenicity, and tumor volume in vivo in CD24 siRNA transfected BCCs. DNA microarray analysis identified STAT1 as a relationship between CD24 and SHH. CD24 siRNA-transfected BCCs with concurrent STAT1 inhibition exhibited decreased SHH expression, invasiveness, anchorage-independent proliferation, tumorigenicity, and tumor volume in vivo . These results suggest that CD24 suppresses development of a malignant phenotype by down-regulating SHH transcription through STAT1 inhibition. CD24 gene transfer or STAT1 inhibition may represent new effective therapeutic strategies to target refractory breast cancer.